TR1801‐ADC: a highly potent cMet antibody–drug conjugate with high activity in patient‐derived xenograft models of solid tumors. Issue 1 (3rd December 2019) - Gymnopoulos, Marco; Betancourt, Oscar; Blot, Vincent; Fujita, Ryo; Galvan, Diana; Lieuw, Vincent; Nguyen, Sophie; Snedden, Jeanette; Stewart, Christine; Villicana, Jose; Wojciak, Jon; Wong, Eley; et al.
Abstract : cMet is a well‐characterized oncogene that is the target of many drugs including small molecule and biologic pathway inhibitors, and, more recently,  antibody–drug conjugates (ADCs). However, the clinical benefit from cMet‐targeted therapy has been limited. We developed a novel cMet‐targeted 'third‐generation' ADC, TR1801‐ADC, that was optimized at different levels including specificity, stability, toxin–linker, conjugation site, and in vivo efficacy. Our nonagonistic cMet antibody was site‐specifically conjugated to the pyrrolobenzodiazepine (PBD) toxin–linker tesirine and has picomolar activity in cancer cell lines derived from different solid tumors including lung, colorectal, and gastric cancers. The potency of our cMet ADC is independent of MET gene copy number, and its antitumor activity was high not only in high cMet‐expressing cell lines but also in medium‐to‐low cMet cell lines (40 000–90 000 cMet/cell) in which a cMet ADC with tubulin inhibitor payload was considerably less potent. In vivo xenografts with low–medium cMet expression were also very responsive to TR1801‐ADC at a single dose, while a cMet ADC using a tubulin inhibitor showed a substantially reduced efficacy. Furthermore, TR1801‐ADC had excellent efficacy with significant antitumor activity in 90% of tested patient‐derived xenograft models of gastric, colorectal, and head and neck cancers: 7 of 10 gastric models, 4 of 10 colorectal cancer models, and 3 of 10 head and neck cancer models showed complete tumor regression after a single‐dose administration. Altogether, TR1801‐ADC is a new generation cMet ADC with best‐in‐class preclinical efficacy and good tolerability in rats. Abstract : TR1801‐ADC is an antibody–drug conjugate with highly potent PBD payload–linker conjugated site‐specifically to our cMet antibody. The ADC is stable in rat circulation with acceptable tolerability. TR1801‐ADC is highly active in MET‐amplified and cMet‐overexpressing cancer cell lines. Patient‐derived xenograft solid tumor models of the stomach, colorectum, and head and neck were highly sensitive to treatment with our anti‐cMet‐ADC.